Mapping global health research investments, time for new thinking - A Babel Fish for research data - Terry Robert F; Allen Liz; Gardner Charles A; Guzman Javier; Moran Mary; Viergever Roderik F (BMC, 2012)
Abstract Today we have an incomplete picture of how much the world is spending on health and disease-related research and development (R&D). As such it is difficult to align, or even begin to coordinate, health R&D investments with international public health priorities. Current efforts to track and map global health research investments are complex, resource-intensive, and caveat-laden. An ideal situation would be for all research funding to be classified using a set of common standards and definitions. However, the adoption of such a standard by everyone is not a realistic, pragmatic or even necessary goal. It is time for new thinking informed by the innovations in automated online translation - e.g. Yahoo's Babel Fish. We propose a feasibility study to develop a system that can translate and map the diverse research classification systems into a common standard, allowing the targeting of scarce research investments to where they are needed most.